Modeling of a pulsed, single cavity Yb–Bi fiber laser taking mode field area mismatch into consideration. (12th February 2019) - Tao, Mengmeng; Feng, Guobin; Luan, Kunpeng; Chen, Hongwei; Shen, Yanlong; Yu, Ting; Ye, Xisheng; Zhao, Jun
Abstract: A theoretical model concerning a pulsed, single cavity Yb–Bi fiber laser is established. A Q-switching rate equation is derived for mode field area mismatch operations. A stable Q-switching wavelength range and corresponding pump range of this laser system is explored, and the detailed population transition processes are described. Further, the pulse characteristics of the laser system are investigated with different pump powers at 1120 nm. The simulations show that, for a single cavity Yb–Bi fiber laser, stable passive Q-switching could be attained in a relatively wide wavelength range, and a relatively larger coupling ratio is more favorable for laser design. At a fixed wavelength, a steady region— where the pulse energy, peak power and pulse duration show little variation with the change of the pump power—exists, and the main cause is the relatively steady effective pump energy in this region.